DIAGENESIS RESERVOIR BATUAN KARBONAT DI LAPANGAN SKW CEKUNGAN JAWA TIMUR UTARA - ERWANTO , EDWARD
Skw oil field is located in Bojonegoro Kota District, Bojonegoro Area, approximately 135 km western of Surabaya City, Jawa Timur Province. Since 2004 the field started produce oil until now with high rate of production which come from carbonate rocks reservoir equivalen Tuban Formation. This carbonate rocks hypothetized have complex facies, diagenesis and porosity which interested to be analized more detail. The main goal of this research is to understand processes which affect and control different porosity value in wells of Skw Field based on diagenesis analysis approach. Research method mainly using macroscopic and microscopic lithology analysis from cutting and core of Skw-1 and Skw-2 wells. Also support by logging, seismic and routine core laboratory test results. From research analyses and interpretation, is resulted that carbonate rocks equivalen Tuban Formation has 2 (two) types facies group consist of first facies group in top depth interval are Planktic-bentic foram bioclastic wackestonepackstone dan Algae bentic foram bioclastic packstone, interbedded coral algae bioclastic wackestone and second facies group in bellow depth interval are Algae bentic foram bioclastic wackestone-packstone and Coral algae bentic foram bioclastic wackestone-packstone. Depositional environment of this carbonate rocks is open lagoon with many patch reefs. Diagenetic process took in place since early diagenetic phase to porosity erotional phase until late burial diagenetic phase. Diagenetic can be seen in shape of dissolution, cementation, vuggy pore to dolomitization and stylolites structure from pressure/compaction. Facies type and development of diagenetic phase, besides of early charging system, are giving strong effect to high or low porosity value distribution of carbonate rocks in this field.